Highly efficient production of the Alzheimer's γ‐Secretase integral membrane protease complex by a multi‐gene stable integration approach123. Issue 7 (15th February 2013) - Alattia, Jean‐René; Matasci, Mattia; Dimitrov, Mitko; Aeschbach, Lorène; Balasubramanian, Sowmya; Hacker, David L.; Wurm, Florian M.; Fraering, Patrick C.
Abstract Inefficient production of membrane‐embedded multi‐protein complexes by conventional methods has largely prevented the generation of high‐resolution structural information and the performance of high‐throughput drug discovery screens for this class of proteins. Not exempt from this rule is γ‐secretase, an intramembrane‐cleaving protease complex regulating a multitude of signaling pathways and biological processes by influencing gene transcription. γ‐Secretase is also implicated in the pathogenesis of Alzheimer's disease and several types of cancer. As an additional challenge, the reconstitution of the protease complex in its active form requires an intricate assembly and maturation process, including a highly regulated endoproteolytic processing of its catalytic component. In this article we report the application of a transposon‐mediated multigene stable integration technology to produce active γ‐secretase in mammalian cells in amounts adequate for crystallization studies and drug screening. Our strategy is expected to help elucidate the molecular mechanisms of intramembrane proteolysis. It is further expected to be widely used for the production of other multi‐protein complexes for applications in structural biology and drug development. Biotechnol. Bioeng. 2013; 110: 1995–2005. © 2013 Wiley Periodicals, Inc.